Energy development in Nigeria and the need for strategic energy efficiency practice scheme for the residential building sector - Hussaini, Ibrahim Udale; Abdul Majid, Noor Hanita (Emerald Group Publishing Ltd., 2015)
Purpose: The purpose of this paper is to seek ways to improve energy efficiency in the residential building sector of Nigeria. This is necessary so as to promote a wider scope of energy efficiency practice in order to reduce energy demand on the central power supply of the nation and as well-attain reasonable level of energy security. Design/methodology/approach: However, the objective of the study is to propose a strategic plan (scheme) of energy efficiency practice for the housing sector of the Nigerian economy. To accomplish this task, a review of the main issues of energy efficiency; the current energy situation in Nigeria; and the challenges to implementing energy efficiency in the country was undertaken. Findings: Finally, remedial measures to achieving energy efficiency in the Nigerian households were proffered by the provision of a "strategic scheme" to be accomplished by the government and the housing stakeholders. Research limitations/implications: It is evident that a strategic plan or framework must be put in place in order to overcome the challenges of energy efficiency in the residential building sector. And this framework is to adequately address the issues of design practice, the efficiency of appliances in use and the housing occupant behaviour. Practical implications: The main goal is the attainment of energy-efficient households in Nigeria through the application of EE practice strategies. Originality/value: The study highlights on the energy development level of the country. It has also identified the numerous barriers as well as the principal actors to achieving energy-efficient households in Nigeria. After all, the suggested "plan of action" as provided in the scheme is to serve as a benchmark and reference point to the government, the housing stakeholders as well as the housing occupant for the attainment of energy efficiency.